(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The objective of the present work was to evaluate the thermal performance of evacuated tube based solar cooker with transformer oil as working fluid. Acetamide is used as phase change material(PCM)to store heat and pass on to the cooking vessel during and after sunlight. Transformer oil is used to transfer heat from evacuated tube to cooking vessel. In the cooking vessel design, there are two concentric cylindrical vessel with insulation provided around the outer cylinder. The outer vessel ishaving PCM and inner vessel as cooking vessel. In the vessel design,copper coil is wrap around the cooking pot. In this work,the system is tested for different load conditions in the cooking vessel during receiving and releasing heat to the PCM. The results are plotted in the form of cooking vessel temperature, PCM temperature, and working fluid temperature in the experimental unit. That gives an idea that the system is capable enough for faster and evening time cooking.